2023
DOI: 10.1007/s00394-023-03293-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations of diet quality and food consumption with serum biomarkers for lipid and amino acid metabolism in Finnish children: the PANIC study

Suvi E. Laamanen,
Aino-Maija Eloranta,
Eero A. Haapala
et al.

Abstract: Purpose To investigate the associations of overall diet quality and dietary factors with serum biomarkers for lipid and amino acid metabolism in a general population of children. Methods We studied 194 girls and 209 boys aged 6–8 years participating in the Physical Activity and Nutrition in Children study. Food consumption was assessed by 4-day food records and diet quality was quantified by the Finnish Children Healthy Eating Index (FCHEI). Fasting serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Poor diet quality is associated with dyslipidemia and metabolic syndrome in children [29]. The PANIC study in Finnish children reported that better diet quality, higher in intake of dietary sources of unsaturated fat were associated with more favorable levels of serum biomarkers for lipid.…”
Section: Correlations Between Serum Lipid Concentrations and Food Cat...mentioning
confidence: 99%
“…Poor diet quality is associated with dyslipidemia and metabolic syndrome in children [29]. The PANIC study in Finnish children reported that better diet quality, higher in intake of dietary sources of unsaturated fat were associated with more favorable levels of serum biomarkers for lipid.…”
Section: Correlations Between Serum Lipid Concentrations and Food Cat...mentioning
confidence: 99%